Data mining: foundations and intelligent paradigms : Volume 2: statistical, bayesian, time series and other theoretical aspects - Jain, Lakhmi C.; Holmes, Dawn E. (Intelligent Systems Reference Library, 2012)
Data mining is one of the most rapidly growing research areas in computer science and statistics. In Volume 2 of this three volume series, we have brought together contributions from some of the most prestigious researchers in theoretical data mining. Each of the chapters is self contained. Statisticians and applied scientists/ engineers will find this volume valuable. Additionally, it provides a sourcebook for graduate students interested in the current direction of research in data mining.